Bacterial Patterns, Causes, and Antibiotic Resistance in Neonatal Sepsis Cases at Yarsi Hospital and its Review from an Islamic Perspective - Amelia Fernanda; Elsye Souvriyanti; Endah Purnamasari; Siti Nur Riani (Eduvest - Journal of Universal Studies, 2026)
Neonatal sepsis is a major cause of newborn morbidity and mortality, especially in developing countries. This systemic bacterial infection can progress rapidly and become fatal without early and appropriate treatment. Effective empirical antibiotic therapy depends critically on the local pattern of causative bacteria and the level of antibiotic resistance within each hospital. This research aims to identify the pattern of bacteria causing neonatal sepsis and analyze bacterial resistance to certain antibiotics based on medical record data, culture results, and antibiotic resistance tests from blood specimens of neonates suspected of having sepsis who were treated at YARSI Hospital during the period 2022-2024. Data was collected by observing and recording medical records of neonatal sepsis patients treated at YARSI Hospital from January 2022 to December 2024. Data analysis was performed in stages using SPSS and Microsoft Excel. The results showed that neonatal sepsis most often occurred in male neonates, was born prematurely, and was dominated by Gram-negative bacteria, especially Klebsiella pneumoniae. Gram-negative bacteria exhibited widespread resistance to first-line antibiotics, while sensitivity to certain antibiotics such as amikacin, tigecycline, and carbapenems was still found. Most cases fell into the multidrug-resistant (MDR) category, indicating a significant challenge in empirical therapy, although no statistically significant association was found between bacterial type and MDR levels. These findings underscore the importance of blood culture and antibiotic sensitivity testing as the basis for appropriate therapy, in line with Islamic values of preserving life, the continuation of generations, and the rational use of antibiotics.